Impacto ambiental decorrente das atividades agrícolas no município do Conde - Paraíba, com ênfase no assentamento rural de Barra de Gramame - Sousa, Breno Henrique de (2005)
In the present work a study on environmental impacts caused by agricultural activities and the identification of potentially degraded or degraded areas resulting from such activities was performed. The study areas selected were the municipality of Conde, located on the south littoral of the State of Paraíba, Northeast Brazil, whose geographical coordinates are lat 07°15 3 S and long 34° 54 27 W, totalling an area of 16,477.3 ha; and the rural settlement of Barra de Gramame, in the north of that municipality, whose geographical coordinates are between lat 7o14 06 and 7o15 32 S, and between long 34o48 37 and 34o51 11 W, totalling an area of 772.17 ha. This work was carried out in two stages: firstly, the most susceptible areas to degradation and the areas unduly exploited were mapped by using topographic charts on the scale of 1:100,000 and by using maps and images from satellite LANDSAT TM-7 scene 214/065, Channels 1, 2, 3, 4, 5, and 7, resolution at 30 m, from August 2001; in the second stage a study on the impact of agricultural practices in the rural settlement was performed and the mapping and evaluation of environmental impact levels were carried out by using topographic chart on the scale of 1:10,000 and images from the satellite SPOT, Channel 4, resolution at 10 m, from August 2001. During both stages, some field visits were carried out, where it was used a GPS (global positioning system) equipment and through a GIS (geographic information system) maps and images were overlaid. The second stage, concerning the rural settlement, was performed in more detail than the first stage. The rural settlement of Barra de Gramame is a representative area of the municipality of Conde, whose results obtained from the second stage contribute to a better knowledge on environmental degradation processes in the whole municipality and also in similar areas on the Brazilian northeastern littoral